Why Syria Goes to War : Thirty Years of Confrontation - Lawson, Fred Haley, 1952- (Book collections on Project MUSE., 1996)
Rejecting conventional explanations for Syrian foreign policy, which emphasize the personalities and attitudes of leaders, cultural factors peculiar to Arab societies, or the machinations of the great powers, Fred H. Lawson describes key shifts in ...